Evaluering van interpersoonlike vaardighede - M. Poggenpoel (AOSIS, 1984)
One of the major goals of nursing is to offer meaningful health services to individuals and groups who need help. This helping process takes place through interpersonal contact between the nurse and individuals and groups. It is important that the nurse has interpersonal skills and training in nursing should also include opportunities for exercising these skills. Observation scales are the most appropriate technique for evaluating the effectiveness of interpersonal skills. There are three types of observation scales: - The anecdotal report: a factual description of a student's behaviour. - Rating scales including numerical rating scales, graphic rating scales and descriptive graphic scales. - Checklists were evaluation of characteristics are limited to a simple present-absent judgement. An instrument (graphic descriptive rating scale) is held as an example of an evaluation instrument that can be used to judge core aspects associated to the nurse's interpersonal skills in a specific situation.